Latent Autoimmune Diabetes in Adults and Metabolic Syndrome—A Mini Review - Pan, Niansi; Yang, Shimei; Niu, Xiaohong (Frontiers in Endocrinology, 2022)
Latent autoimmune diabetes in adults (LADA) is a heterogeneous subtype of diabetes, which is characterized by islet cell destruction mediated by islet autoimmunity and insulin resistance. Metabolic Syndrome (MetS) is a state in which many metabolic and cardiovascular risk factors accumulate in an individual. The purpose of this review is to provide an overview of the prevalence of MetS in LADA, meanwhile, to discuss the risk and role of insulin resistance in LADA patients from the aspects of inflammatory factors, environmental and gut microbiota factors, so as to improve our understanding of LADA.